Simultaneous Measurement of νμ Quasielasticlike Cross Sections on CH, C, H2 O, Fe, and Pb as a Function of Muon Kinematics at MINERvA - Kleykamp, J.; Akhter, S.; Ahmad Dar, Z.; Ansari, V.; Ascencio-Sosa, M.V.; Athar, M.; Bashyal, A.; Bercellie, A.; Betancourt, M.; Bodek, A.; Bonilla, J.L.; Bravar, A.; et al. (American Physical Society, 2023)
This Letter presents the first simultaneous measurement of the quasielasticlike neutrino-nucleus cross sections on C, water, Fe, Pb, and scintillator (hydrocarbon or CH) as a function of longitudinal and transverse muon momentum. The ratio of cross sections per nucleon between Pb and CH is always above unity and has a characteristic shape as a function of transverse muon momentum that evolves slowly as a function of longitudinal muon momentum. The ratio is constant versus longitudinal momentum within uncertainties above a longitudinal momentum of 4.5 GeV/c. The cross section ratios to CH for C, water, and Fe remain roughly constant with increasing longitudinal momentum, and the ratios between water or C to CH do not have any significant deviation from unity. Both the overall cross section level and the shape for Pb and Fe as a function of transverse muon momentum are not reproduced by current neutrino event generators. These measurements provide a direct test of nuclear effects in quasielasticlike interactions, which are major contributors to long-baseline neutrino oscillation data samples.
Keywords: Physics; Muon; Nuclear physics; Momentum (technical analysis); Neutrino; Muon neutrino; Nucleon; Particle physics; Neutrino oscillation; Neutrino detector; https://purl.org/pe-repo/ocde/ford#1.03.04